Literacy as Danger in George Orwell’s Nineteen Eighty-Four - Edwin Anugerah Pradana (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2022)
Literacy has always being considered to be empowering for some people. However, literacy can also serve as danger. This study aims to reveal how Winston Smith as the main character in George Orwell‘s Nineteen Eightyfouruses reading and writing activities that brings danger to the character‘s life. Employing Marxism approach in rebellion and New Literacy Studies concept of literacy as social practice, this study reveals that Winston Smith carries out various readings and writings activities which considered as danger to his life. Literacy in the novel Nineteen Eighty-four can be categorized as a dangerous literacy process that leads to rebellion process of Winston Smith. First, the literacy process carried out by Winston Smith's character is illustrated by the emergence to write a diary which is actually considered as a prohibited activity in his country. Second, the danger of literacy process in the form of reading appears an option to rebel, emerged and brought by a book entitled Oligarchy Theory and Practice of Collectivism, which was written by a rebellious figure named Emmanuel Goldstein. Winston Smith uses those practices to rebel against his country for the abuse of power. This rebellion leads to a danger in which the main character, Winston Smith, is punished.